Liquid–liquid extraction intensification with magnetite nanofluid single drops under oscillating magnetic field - Saien, Javad; Bamdadi, Hamid; Daliri, Shabnam (Journal of industrial and engineering chemistry (Seoul, Korea), 2015)
The influence of an oscillating magnetic field was investigated in mass transfer from magnetite nanofluid single drops in liquid–liquid extraction process. The chemical system of toluene–acetic acid–water was used, while hydrophobic magnetite nanoparticles were present in the organic dispersed phase. The magnetic field intensity was within the range of 0.36–1.45T, accompanied with different nanofluid concentrations within 0.001–0.005wt%. Compared with no magnetic field, an average enhancement of about 65% and a maximum of 121% (for the smallest used drops) were achieved. This essential matter can be attributed to the induced nanoparticles micro-convection inside the drops.